In situ AP-XPS study on reduction of oxidized Rh catalysts under CO exposure and catalytic reaction conditions. (2nd March 2021) - Toyoshima, Ryo; Ueda, Kohei; Koda, Yuki; Kodama, Hiroshi; Sumida, Hirosuke; Mase, Kazuhiko; Kondoh, Hiroshi
Abstract: Reduction of oxidized Rh catalysts under carbon monoxide (CO) exposure and reaction conditions were studied by using ambient-pressure x-ray photoelectron spectroscopy. First, Rh powders pressed into a pellet were deeply oxidized and the reduction process under 100 mTorr CO environment was monitored in situ at different temperatures. The oxidized Rh surfaces are composed of Rh2 O3 and RhO2, the latter of which is more segregated near the surface. Both oxide species are reduced simultaneously to the metallic state; kinetic analyses indicate that the activation energy of the reduction of the Rh oxides is 1.68 eV, which is a little larger than those for Pd oxides, probably due to a stronger Rh–O interaction. Reduction of oxidized Rh nano-particles deposited on SiO2 under two reaction conditions (CO + O2 and CO + NO + O2 ) was observed with increasing temperature. It was found that the reduction temperature shifts to the higher temperature in the presence of NO, even though the S -factors are almost the same. The NO molecule more strongly prevents the reduction of oxidized Rh catalyst compared to O2 .